EXPLORING THE INFLUENCE OF PROFITABILITY, LEVERAGE, CAPITAL INTENSITY, AND FIRM SIZE ON TAX AVOIDANCE IN INDONESIA - Fila Elkaria; Setyo Mahanani; Mohamad Hazeem Sidik (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Tax avoidance refers to the strategic practices employed by companies to legally minimize their tax obligations by taking advantage of legal loopholes or exemptions. Indonesia’s tax ratio ranks as the third lowest among Asia-Pacific nations and remains below the international standard of 15%, falling short of the ideal level for the country. Therefore, this study investigates the influence of profitability, leverage, capital intensity, and company size on tax avoidance among consumer goods firms listed on the Indonesia Stock Exchange during the period from 2020 to 2022. The study utilized purposive sampling, resulting in a sample of 80 out of 124 consumer firms. The data were analysed using multiple linear regression in IBM SPSS version 26. The findings indicate that while leverage, capital intensity, and company size did not have a significant effect on tax avoidance, profitability exhibited a negative relationship with tax avoidance. Future research can focus on the variables such as ownership structure, corporate governance, political connections, audit quality, managerial ownership, and transparency. Managers (agents) and shareholders (principals), driving managers to engage in tax avoidance to meet performance targets and reduce agency costs.